A prospective study on osmophobia in migraine versus tension-type headache in a large series of attacks. (April 2020) - Terrin, Alberto; Mainardi, Federico; Lisotto, Carlo; Mampreso, Edoardo; Fuccaro, Matteo; Maggioni, Ferdinando; Zanchin, Giorgio
Background: In literature, osmophobia is reported as a specific migrainous symptom with a prevalence of up to 95%. Despite the International Classification of Headache Disorders 2nd edition proposal of including osmophobia among accompanying symptoms, it was no longer mentioned in the ICHD 3rd edition. Methods: We conducted a prospective study on 193 patients suffering from migraine without aura, migraine with aura, episodic tension-type headache or a combination of these. After a retrospective interview, each patient was asked to describe in detail osmophobia, when present, in the following four headache attacks. Results: In all, 45.7% of migraine without aura attacks were associated with osmophobia, 67.2% of migraineurs reported osmophobia in at least a quarter of the attacks. No episodic tension-type headache attack was associated with osmophobia. It was associated with photophobia or phonophobia in 4.3% of migraine without aura attacks, and it was the only accompanying symptom in 4.7% of migraine without aura attacks. The inclusion of osmophobia in the ICHD-3 diagnostic criteria would enable a 9.0% increased diagnostic sensitivity. Conclusion: Osmophobia is a specific clinical marker of migraine, easy to ascertain and able to disentangle the sometimes challenging differential diagnosis between migraine without aura and episodic tension-type headache. We recommend its inclusion among the diagnostic criteria for migraine as it increases sensitivity, showing absolute specificity.